Discourse of the Other in Agatha Christie’s An Autobiography - Ramazan, F. J. R. (Видавництво НДУ імені Миколи Гоголя, 2020)
The paper discusses Jacques Lacan’s discourse of the other, relevant to the authority of societal influence and the creation of a person’s ego and alter egos. In this theory Lacan refers to the little others (i. e. the ego and alter egos) and the big Others (i. e. points of authority, societal expectations, and cultural norms). Studying one’s psychological makeup and development is a process that can be quite invasive and lengthy. However, there is a genre of literature that focuses directly on authors’ personal and introspective views of their own lives. Autobiographies are books in which authors write about their own personal experiences. They can include information about a person’s childhood, their upbringing, the beginning of their career path, or any other life periods they deem notable enough. Thus the paper will look at Agatha Christie’s autobiography from the perspective of Lacanian ideas. Christie’s childhood is an exceptional example of how Lacan’s theories explain children’s desires and how they are shaped by the environment and authority figures around them. Christie would not have begun reading books well before her mother wanted her to if Nursie had not begun reading her stories. Likewise, she probably would not have been interested in doing math problems at such a young age if her wealthy father had not given her such positive feedback over her desire to learn academics as a young girl. The developments of Christie are unique to her own environment and situation; and there are many other people who have developed in other ways due to the authority figures around them. In the future, Lacan scholars may want to look at more autobiographies to see if the discourse of the Other presents itself.
Keywords: discourse of the Other; big Other; little other